Mentalinis dvilypumas, kylantis iš prieštaros lokalus–globalus - Krikštopaitis, Juozas Algimantas (Journal of Architecture and Urbanism, 2007)
Mental duality emerging from local-global contradiction The paper discusses the phenomenon of mental duality which emerges when a person, upon entering a community of a different cultural and historic experience, seeks to be admitted to citizenship thus realizing possibilities for his activity. However, this phenomenon of duality appears even when a person does not leave his native country. The matter is that a foreign culture surging into a person’s native domain can turn him into an emigrant in his own home. The phenomenon of emigration (exile) is discussed, while examining the resulting activities of distinguished members of the Lithuanian diaspora. A conclusion is made that in the present globalized and urbanized world it is impossible to avoid such a mental duality. The author suggests nurturing of the signs of uniqueness in creativity based on native cultural values. That would reduce stress due to mental duality. Article in Lithuanian. Santrauka. Mentalinis dvilypumas, kylantis iš prieštaros lokalus–globalus Aptariamas mentalinio susidvejinimo reiškinys, kai asmuo, patekęs į kitos kultūros ir kitos istorinės patirties visuomenę, siekia joje įsipilietinti ir realizuoti savo galimybes. Tačiau susidvejinimo reiškinys atsiranda net ir tuomet, kai žmogus neiškeliauja kitur. Reikalas tas, kad kita kultūra, įsiveržusi į gimtąjį arealą, gali žmogų paversti išeiviu jo paties namuose. Išeivystės (egzilės) reiškinys aptariamas nagrinėjant žymių Lietuvos išeivių veiklos rezultatus. Daroma išvada, kad dabarties globaliai urbanizuotame pasaulyje mentalinio susidvejinimo išvengti neįmanoma. Autorius siūlo puoselėti kūrybinės raiškos unikalumo požymius, remiantis gimtosios kultūros vertybėmis. Toks kelias padėtų švelninti mentalinio susidvejinimo įtampą. Reikšminiai žodžiai: lokalus, globalus, išeivystė, mentalinis dvilypumas, ištikimybė. First published online: 21 May 2013